2004
DOI: 10.1111/j.1440-6055.2004.00402.x
|View full text |Cite
|
Sign up to set email alerts
|

Mass rearing of two larval parasitoids of Helicoverpa spp. (Lepidoptera: Noctuidae): Netelia producta (Brullé) and Heteropelma scaposum (Morley) (Hymenoptera: Ichneumonidae) for field release

Abstract: Parasitoids are becoming an increasingly important part of our biological arsenal in Integrated Pest Management strategies against major insect pests like Helicoverpa armigera (Hübner). Inundative or supplementary releases of parasitoids have been successfully used in the past to help manage insect pests in the field. This paper reports attempts to mass rear two larval parasitoids of Helicoverpa spp., Heteropelma scaposum and Netelia producta . The results suggest that N. producta is the easier species to cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…Often females control sex allocation directly. Most non-social haplodiploid species are parasitoids and have sex ratios ranging from highly male-biased 28 to highly female-biased 29 . In sexually reproducing diplodiploid species, sex ratio biases of intrinsic genetic origin (e.g., not due to manipulation by endosymbionts) are extremely rare 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Often females control sex allocation directly. Most non-social haplodiploid species are parasitoids and have sex ratios ranging from highly male-biased 28 to highly female-biased 29 . In sexually reproducing diplodiploid species, sex ratio biases of intrinsic genetic origin (e.g., not due to manipulation by endosymbionts) are extremely rare 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Another parasitoid of Helicoverpa spp. larvae in Australia, the ichneumonid Netelia producta (Brullé), is known to lay its external eggs just behind the head capsule and it is thought that this done so that they could not be removed by the host's mandibles (Johns & Whitehouse 2004). The observed differences in the point of entry of planidia in H. punctigera and H. armigera larvae is difficult to explain but may again relate to differences in cuticle toughness.…”
Section: Discussionmentioning
confidence: 99%
“…Further research on the biology and ecology of C. dorsalis is warranted to investigate its potential for mass rearing and releasing to control Helicoverpa spp. Previous studies on lepidopteran parasitoids in Australia have concentrated on the amenability of mass rearing hymenopterans (Johns & Whitehouse 2004). However, this study has demonstrated that C. dorsalis is relatively easy to rear in the laboratory and may be amenable to mass rearing for field release using similar methods developed by Gross (1994) for A. marmoratus whereby planidia were mechanically extracted from fecund females and applied as an aqueous suspension onto crops.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations